Dissecting the interaction of photosynthetic electron transfer with mitochondrial signalling and hypoxic response in the Arabidopsis rcd1 mutant - Shapiguzov, Alexey; Nikkanen, Lauri; Fitzpatrick, Duncan; Vainonen, Julia P; Gossens, Richard; Alseekh, Saleh; Aarabi, Fayezeh; Tiwari, Arjun; Blokhina, Olga; Panzarová, Klára; Benedikty, Zuzana; Tyystjärvi, Esa; et al. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2020)
The Arabidopsis mutant rcd1 is tolerant to methyl viologen (MV). MV enhances the Mehler reaction, i.e. electron transfer from Photosystem I (PSI) to O2, generating reactive oxygen species (ROS) in the chloroplast. To study the MV tolerance of rcd1, we first addressed chloroplast thiol redox enzymes potentially implicated in ROS scavenging. NADPH-thioredoxin oxidoreductase type C (NTRC) was more reduced in rcd1. NTRC contributed to the photosynthetic and metabolic phenotypes of rcd1, but did not determine its MV tolerance. We next tested rcd1 for alterations in the Mehler reaction. In rcd1, but not in the wild type, the PSI-to-MV electron transfer was abolished by hypoxic atmosphere. A characteristic feature of rcd1 is constitutive expression of mitochondrial dysfunction stimulon (MDS) genes that affect mitochondrial respiration. Similarly to rcd1, in other MDS-overexpressing plants hypoxia also inhibited the PSI-to-MV electron transfer. One possible explanation is that the MDS gene products may affect the Mehler reaction by altering the availability of O2. In green tissues, this putative effect is masked by photosynthetic O2 evolution. However, O2 evolution was rapidly suppressed in MV-treated plants. Transcriptomic meta-analysis indicated that MDS gene expression is linked to hypoxic response not only under MV, but also in standard growth conditions. This article is part of the theme issue 'Retrograde signalling from endosymbiotic organelles'.
Keywords: Photosynthesis; Mitochondria; signální transdukce; Signal Transduction; proteiny huseníčku; anaerobióza; Anaerobiosis; Arabidopsis thaliana; jaderné proteiny; Arabidopsis Proteins; mitochondrie; Arabidopsis; Nuclear Proteins; reactive oxygen species; transport elektronů; retrograde signalling; hypoxia; fotosyntéza; photosynthetic electron transfer; Electron Transport; mitochondrial dysfunction stimulon